PERAN PEMDA DALAM MELAKSANAKAN PROGRAM PEMBANGUNAN MANUSIA DAN IMPLIKASINYA TERHADAP KETAHANAN WILAYAH (Studi di Kabupaten Bone Bolango Provinsi Gorontalo) - Lukum, Roni (Jurnal Legalitas, 2012)
His research was conducted with the aim of: (1). How public opinion on the role of local governments in implementing human development programs in the area Bone Bolango. (2). How does the human development implications of regional recilience in the region Bolango Bone regency. The method used in this study is a joint survey with the analysis of qualitative and quantitative. This research was conducted in the Bone Bolango. Respondents in this study carried out by taking aim sampling (purposive sampling). Number of respondents 61 people, spread in all districts. The results showed that (1). The size of the Regional IPM Bone Bolango health life expectancy in the year 2007 the score was 67.60 years beyond the Gorontalo provincial standards only 65.90 years, education literacy rate has increased by a score of 97.10 exceed the standards only 95.70 Gorontalo province, per capita expenditure of Bone Bolango are in third place position with numbers reaching 609.31 per capita expenditure has not exceeded the standard Gorontalo province USD 615.94 (2). Public opinion about the role of local governments in implementing human development programs obtained very satisfactory results as much as 90.48%, and the assessment is very weak only 9:52%. (3). The results of the application Human Development Program (IPM) has a positive impact on the economy, politics and ideology, social, cultural and security in the region of Defense Bone Bolango, this is shown by the stability condition that until now was a good or conducive.